One Pot Synthesis of Micromolar BACE-1 Inhibitors Based on the Dihydropyrimidinone Scaffold and Their Thia and Imino Analogues - Jessica Bais; Fabio Benedetti; Federico Berti; Iole Cerminara; Sara Drioli; Maria Funicello; Giorgia Regini; Mattia Vidali; Fulvia Felluga (Molecules, 2020)
A library of dihydropyrimidinones was synthesized via a “one-pot” three component Biginelli reaction using different aldehydes in combination with β-dicarbonyl compounds and urea. Selected 2-thiooxo and 2-imino analogs were also obtained with the Biginelli reaction from thiourea and guanidine hydrochloride, respectively. The products were screened in vitro for their β-secretase inhibitory activity. The majority of the compounds resulted to be active, with IC50 in the range 100 nM–50 μM.